Recent environmental change as recorded in Godthåbsfjorden sediments, Western Greenland - O´Brien, Elaina Mary, 1991- (2021)
Effects of environmental and climate change are evident from seven sediment cores taken in the Godthåbsfjord, West Greenland. Continuous smear slides taken from these sediment cores reveal signals of increasing fine mineral grain sizes (very fine silt and clay) and increasing concentrations of terrestrial organic matter throughout the last decades, especially at locations close to the glacier outlets from the Greenland ice sheet in the east and at locations taken at intermediate distance between the glacier outlets and the western fjord outlet at Nuuk, the capital of Greenland. Both signals were interpreted as originating from glacial retreat due to glacial melting (finer grain sizes), and from erosional processes occurring at newly exposed and more overgrown icefree land surfaces (terrestrial organic matter). Heavy metal, PAH, and PCB concentration were found at background or slightly elevated non-polluting levels, apart from polluting concentrations of nickel originating from the local rocks surrounding the Godthåbsfjord. Contaminant patterns in the middle and western parts of the fjord follow the distribution pattern of the fine mineral grain sizes and the terrestrial organic matter concentrations indicating contaminant sources from land deposits and settlements at Nuuk, Qoornoq, and Kapisillit. Contaminant pattern in the easternmost sediment core is related to coarse mineral grain sizes (coarse silt and fine sand) and the marine organic matter concentration, indicating their sources originating from glacial runoff of air transported contaminant that deposited on the Greenland ice sheet. The overall correlation of contaminants with sediment parameters over the last decades allows the conclusion that future contaminant scenarios might turn into pollution scenarios in the Godthåbsfjord sediments if global warming continues to increase the supply of sediment parameters related to the contaminant distribution, namley fine-grained and organic matter. Umhverfis- og loftlagsáhrif eru bersýnileg úr sjö setkjörnum ...